Notes on the planning, design, materials and construction of settlements for low-income group. - Yeang, Ken (My University, 1983)
Anmerkungen zu Kriterien fuer Konzeption, Materialwahl und Zielvorgabe einer sozialen Wohnungsbaupolitik in Malaysien. ACA
Keywords: Wohnen/Wohnung; Wohnform; Wohnungsbaupolitik; Low-Cost-Housing